Interferon-induced guanylate-binding proteins in inflammasome activation and host defense - Kim, Bae-Hoon; Chee, Jonathan D; Bradfield, Clinton J; Park, Eui-Soon; Kumar, Pradeep; MacMicking, John D (Nature immunology, 2016)
In this Perspective, MacMicking and colleagues discuss the roles of interferon-induced guanylate-binding proteins in directing inflammasome responses and their effects on immunity to a wide variety of microbial pathogens. Traditional views of the inflammasome highlight the assembly of pre-existing core components shortly after infection or tissue damage. Emerging work, however, suggests that the inflammasome machinery is also subject to 'tunable' or inducible signals that might accelerate its autocatalytic properties and dictate where inflammasome assembly takes place in the cell. Many of these signals operate downstream of interferon receptors to elicit inflammasome regulators, including a new family of interferon-induced GTPases called 'guanylate-binding proteins' (GBPs). Here we investigate the critical roles of interferon-induced GBPs in directing inflammasome subtype–specific responses and their consequences for cell-autonomous immunity to a wide variety of microbial pathogens. We discuss emerging mechanisms of action and the potential effect of these GBPs on predisposition to sepsis and other infectious or inflammatory diseases.